Discovery Learning Model As a Forum For Emancipatory Thinking in Social Studies Learning In Digital Era - Felia Siska; Irwan Irwan; Asnimawati; Maria Magdalena Beatrice Sogen; Neffi Sulkaisi (Criksetra: Jurnal Pendidikan Sejarah, 2025)
The purpose of this writing is to analyze the learning model of discovery learning as a forum for emancipatory thinking in social studies learning in the digital era. The research method used is Library Reasearch. The results showed that the discovery learning model is needed in social studies learning both at the elementary school level in the digital era. Through this model, students are able to think critically and have creativity in solving problems and connecting social phenomena that occurred in the past. In addition, being able to improve critical ways of thinking and provide opportunities for students to develop creativity in Social Studies learning in the present condition by thinking emancipatorically, this way of thinking departs from the critical theory developed by Jurgen Habermas of the Frankfurt School. This thinking raises the question of emancipatory as a link between the past and the present so that students are able to take the right creative development in solving problems.